2021
DOI: 10.1108/ijlm-11-2020-0453
|View full text |Cite
|
Sign up to set email alerts
|

The impacts of sustainable inter-firm collaboration on business performance of shipping companies

Abstract: PurposeTo gain competitive advantage, shipping companies need the abilities to manage environmental requirements, which this study refers to as sustainable shipping capabilities, including internal resources and external factors such as inter-firm collaboration. However, previous studies mainly focused on the effectiveness of internal resources, leading decision-makers in shipping companies to undervalue the significance of external relationships in managing sustainability issues and their impact on performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 67 publications
1
10
0
Order By: Relevance
“…Upstream interfirm capabilities concern a firm's ability to jointly leverage and deploy both firm and supplier resources to effect mutually beneficial outcome(s); downstream interfirm capabilities concern a firm's ability to jointly leverage and deploy both firm and customer resources to effect mutually beneficial outcome(s). Notably, because some papers were unclear regarding whether the interfirm capability was upstream or downstream, we classified some capabilities as interfirm capabilities, which could involve customer and/or supplier (Iyer et al, 2019; Seggie et al, 2006; Tran et al, 2021). Additionally, a key distinguishing factor between interfirm capabilities and network capabilities is that interfirm capabilities involve dyadic relationships, whereas network capabilities concern “a system of mutual relationships between at least three parties […] organized by an interconnective web of relationships” (Bagozzi, 1975, p. 33).…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…Upstream interfirm capabilities concern a firm's ability to jointly leverage and deploy both firm and supplier resources to effect mutually beneficial outcome(s); downstream interfirm capabilities concern a firm's ability to jointly leverage and deploy both firm and customer resources to effect mutually beneficial outcome(s). Notably, because some papers were unclear regarding whether the interfirm capability was upstream or downstream, we classified some capabilities as interfirm capabilities, which could involve customer and/or supplier (Iyer et al, 2019; Seggie et al, 2006; Tran et al, 2021). Additionally, a key distinguishing factor between interfirm capabilities and network capabilities is that interfirm capabilities involve dyadic relationships, whereas network capabilities concern “a system of mutual relationships between at least three parties […] organized by an interconnective web of relationships” (Bagozzi, 1975, p. 33).…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…A search on the Web of Science Core Collection database [43], topic sustainable shipping, is composed of 35 scientific papers published in the last two years, 2020 and 2021 [1,2,6,8,9,10,11,12,13,14,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,37,39,40,41,42]. Topic search used for this purpose was ''sustainable shipping'' or sustainable shipping*.…”
Section: Methodsmentioning
confidence: 99%
“…They also revealed that the researched companies are more likely to have implemented both types of supply chain practices -environmental and social, then just one of them. Tran et al (2021) showed that the existence of financial, social and structural bonds in relationships of shipping companies in Vietnam has impact on their sustainable cooperation. Nath and Agrawal (2020), based on their research of Indian manufacturing sector, conclude that supply chain agility and lean management practices may act as antecedents of supply chain social sustainability.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These approaches can also have a significant impact on the extent to which links in the supply chain cooperate when implementing sustainable development initiatives. Some of the previous studies were targeted at determination of the antecedents of inter-firm supply chain cooperation in the implementation of sustainability initiatives, revealing, for example, that the internal imple-mentation of sustainable development initiatives, governance board characteristics (Sebastianelli & Tamimi, 2020), existence of various bonds in relationships (Tran et al, 2021), or management and work organisation methods (Nath & Agrawal, 2020) impact their implementation at the supply chain level. However, to my best knowledge, no research has verified whether companies can have different approaches to cooperation in the supply chain when implementing sustainable development initiatives, i.e., whether they generally strive to cooperate in this area or usually try to implement them on their own.…”
Section: Introductionmentioning
confidence: 99%